CHARACTERISTIC, ORIGINAL AND FORMING CONDITION OF GRAINED SEDIMENTS IN SURFICIAL SEDIMENTS OF TONKIN GULF - Thanh, Dinh Xuan; Nghi, Tran; Lan, Nguyen Thanh; Tha, Hoang Van (Vietnam Journal of Marine Science and Technology, 2008)
Based on original characteristics, the grained size surficial sediments on bottom Tonkin Gulf was divided into 3 groups: provenance of sediments related to igenous and sedimentwy rocks, provenance of sediments are materials of late Pleistocene weathering crust and provenance of bioturbance materials. Especially, the second group was detailed classified by mineral and chemical compositions, such as: lateritzed curdles, clastics rich in iron, clastics rich in Ca; and iron, cancite clatics. Sediments what originated from igenous and sedimentaJy rock are distributed around Bach Long Vi Island at 50 - 60 water depth. They were supplied from Bach Long Vi Island or continental. The continental provenance of sediment was transported by ancient river systems what formed in the regression phase in late Pleistocene (Q13b). Destroyed weathering crustal sediments are originated from uppermost of late Pleistocene marine sediments (m Q13b) what affected by marine wave dynamic in Flandrian transgression phase.